Usefulness of (18)F-fluorodeoxyglucose positron emission tomography/computed tomography in dermatofibrosarcoma protuberans on treatment with imatinib - Kashyap, Raghava (Indian J Nucl Med, 2016)
Dermatofibrosarcoma protuberans (DFSP) is a rare locally aggressive tumor with distant metastases being unusual. We present a case of metastatic DFSP treated with imatinib showing complete metabolic response to treatment.